Economic-environmental assessment of silvo-pastoral systems in Colombia: An ecosystem service perspective - Sandoval, Danny; Florez, Jesús F.; Enciso, Karen; Sotelo Cabrera, Mauricio Efren; Burkart, Stefan (Elsevier, 2023)
Cattle production in Colombia has an important social and economic role but causes considerable environmental impacts, such as deforestation and greenhouse gas emissions by ruminants, particularly methane. Thus, technological innovations aimed at reducing these impacts must focus on both economic and environmental sustainability. Silvo-pastoral systems (SPS) offer productivity increases while generating environmental benefits and ecosystem services and are therefore at the center of debate around sustainable production alternatives. The objective of this article is to evaluate the economic-environmental performance of two proposed SPS for a cattle fattening system for the Colombian context: (i) Urochloa brizantha cv. Toledo and (ii) Urochloa hybrid cv. Cayman, both in association with Leucaena leucocephala trees for browsing and shade provision. They are compared with the respective base scenarios of only using the grasses in monocultures. The study consists of a financial analysis, which estimates potential profitability increases in beef production in the SPS, and an environmental evaluation, which estimates the monetary values of microclimatic regulation and reduction of methane emissions. The value of methane emission reductions is then integrated into a combined economic-environmental evaluation. Results show that both SPS improve the profitability indicators of the production system and reduce the probability of economic loss. Likewise, the reduction of methane emissions in the SPS is estimated at US$6.12 per cattle, and the economic value of microclimatic regulation at US$2,026 per hectare.